Finally, inkjet-printed metal halide perovskite LEDs – utilizing seed crystal templating of salty PEDOT:PSS. Issue 7 (2nd June 2020) - Hermerschmidt, Felix; Mathies, Florian; Schröder, Vincent R. F.; Rehermann, Carolin; Morales, Nicolas Zorn; Unger, Eva L.; List-Kratochvil, Emil J. W.
Abstract : Light-emitting diodes with an inkjet-printed active layer based on MAPbBr3 perovskite are produced for the first time. Abstract : Solution-processable metal halide perovskites are increasingly implemented in perovskite-based light-emitting diodes (PeLEDs). Especially green PeLEDs based on methylammonium lead bromide (MAPbBr3 ) composites exhibit impressive optoelectronic properties, while allowing processing by low-cost and upscalable printing methods. In this study, we have investigated the influence of potassium chloride (KCl) blended into the common hole injection material poly(3, 4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) to boost PeLED device performance. The inclusion of KCl firstly results in a change in morphology of the PEDOT:PSS layer, which then acts as a template during deposition of the perovskite layer. A MAPbBr3 :polyethylene glycol (PEG) composite was used, which does not require the deposition of an anti-solvent droplet to induce preferential perovskite crystallization and is therefore suitable for spin coating and scalable inkjet printing processes. PeLEDs utilizing the KCl induced templating effect on a planar PEDOT:PSS/MAPbBr3 :PEG architecture show improved performance, predominantly due to improved crystallization. PeLEDs incorporating spin-coated perovskite layers yield a 40-fold increase in luminance (8000 cd m −2 ) while the turn-on voltage decreases to 2.5 V. KCl-modified PEDOT:PSS contact layers enabled the realization of inkjet-printed PeLEDs with luminance increased by a factor of 20 at a maximum of 4000 cd m −2 and a turn-on voltage of 2.5 V. This work paves the way for inkjet-printed perovskite light-emitting devices for a wide variety of low-cost and customizable applications.